Faktor - Faktor Yang Mempengaruhi Penyaluran Pembiayaan Perbankan Syariah Indonesia Periode 2009 - 2019 - Warto Warto; R Bambang Budhijana (Prodi Perbankan Syariah FAI UMT, 2019)
Compared to conventional banking, the distribution of Islamic banking financing is more optimal, growth is continuous and asset enhancement is very good. This is indicated by the Financing to Deposit Ratio (FDR) which ranges between 94.88%. This means that a Sharia Bank is able to meet the targets and expectations of Bank Indonesia. Given the lack of Islamic banks and their limited assets, this optimization is certainly influenced by many factors, therefore it is necessary to test the factors that influence the distribution of Islamic banking financing, which includes Third Party Funds (DPK), Non Performing Financing (NPF) and Bank Indonesia Syariah Certificate (SBIS). This study uses the Sharia Commercial Bank and the Sharia Business Unit as a whole as a unit of research object, with the research period from 2009-2019 (in the quarterly period). The analysis technique used is multiple linear regression, while hypothesis testing uses the t-test to test the effect of variables partially, and the F-test to test the effect of variables simultaneously with a significance level of 5% or 0.05. Based on the research, it was found that Third Party Funds (TPF) had a positive and significant effect on the distribution of Islamic Banking financing. Non Performing Financing (NPF) has a positive and insignificant effect on the distribution of bank financing. While Sharia Bank Indonesia Certificates (SBIS) have a negative and significant effect on the distribution of bank financing.